2021
DOI: 10.1044/2021_persp-20-00239
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Narrative Language Intervention on the Language Skills of Children With Hearing Loss

Abstract: Purpose Narrative intervention has not been extensively investigated with children with hearing loss, but it has been shown to improve a broad range of language skills of children with a variety of disabilities and language needs. Therefore, the purpose of this study was to investigate the effect of narrative language intervention on the narrative retelling skills and vocabulary use of children with hearing loss. Method A multiple baseline design (for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, only a few studies have tested the effectiveness of intervention strategies for children with HL. For example, studies have shown that explicit and direct instruction (Lund & Douglas, 2016;Lund & Schuele, 2014), meaningoriented auditory training (Barcroft et al, 2021), and teaching words embedded in narratives (Raymond & Spencer, 2021) are effective strategies for teaching new words to children with HL.…”
Section: Retrieval Practice and Word Learningmentioning
confidence: 99%
“…However, only a few studies have tested the effectiveness of intervention strategies for children with HL. For example, studies have shown that explicit and direct instruction (Lund & Douglas, 2016;Lund & Schuele, 2014), meaningoriented auditory training (Barcroft et al, 2021), and teaching words embedded in narratives (Raymond & Spencer, 2021) are effective strategies for teaching new words to children with HL.…”
Section: Retrieval Practice and Word Learningmentioning
confidence: 99%